A&T India Maternal Nutrition Endline Survey 2019: Households - Recently Delivered Women - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
This dataset is the result of the household/recently delivered women (RDW) survey that was conducted to gather data for the endline part of the impact evaluation study of the Alive & Thrive (A&T) interventions delivered through the Reproductive, Maternal, Newborn, Child Health (RMNCH) services in India. These include provision of iron and folic acid (IFA) and calcium supplements, interpersonal counseling on diet during pregnancy and consumption of IFA and calcium, community mobilization, and adequate weight-gain monitoring during pregnancy. A&T is a global initiative that supports the scaling up of nutrition interventions to save lives, prevent illnesses, and contribute to healthy growth and development through improved maternal nutrition, breastfeeding, and complementary feeding practices. Using a cluster-randomized evaluation design, the primary objectives of the A&T evaluation study in India are to answer the following questions : (1) Can the coverage and utilization of key maternal nutrition interventions be improved by integrating nutrition-focused social behavior change (SBC) communication and systems strengthening approaches into antenatal care (ANC) services under the RMNCH program? (2) What factors affect effective integration of maternal nutrition interventions into a well-established government ANC service delivery platform under the RMNCH program? (3) What are the impacts of the program on i) consumption of diversified foods and adequate intake of micronutrient, protein, and energy compared to recommended intake; ii) intake of IFA and calcium supplements during pregnancy; iii) weight gain monitoring; and iv) early initiation of breastfeeding. As with the baseline, the endline survey used the same 26 blocks in Uttar Pradesh. Thirteen blocks from two districts (Kanpur Dehat and Unnao) were randomly allocated to receive intensified maternal nutrition interventions. Another 13 blocks from the same two districts were randomly allocated to the comparison groups. The survey took place between November and December 2019 by the team from International Food Policy Research Institute (IFPRI), in collaboration with the survey firm, NEERMAN (Network for Engineering and Economics Research and Management). The endline survey comprised 11 questionnaires: 1) Household questionnaire for recently delivered women (RDW) with children <6 months of age, 2) Household questionnaire for pregnant women (PW) of the second and third trimester of pregnancy (with detailed dietary recall), 3) Household questionnaire for husbands of PWs and husbands of RDWs, 4) Household questionnaire for mothers/mothers-in-law of PWs and mothers/mothers-in-law of RDWs, 5) Frontline health workers: Anganwadi workers (AWW), 6) Frontline health workers: Accredited Social Health Activist (ASHA), 7) Frontline health workers: Auxiliary Nurse Midwife (ANM), 8) Frontline health workers: Supervisor (SUP), 9) Observation: AWW, 10) Observation: ASHA, and 11) Observation: ANM. The household survey for recently delivered women (RDW) captured the main impact indicators for A&T (consumption of IFA and calcium, maternal dietary diversity, quantity and quality of diet, breastfeeding practices), use of ANC services and exposure to A&T’s intervention platforms, and a variety of other data related to the use of the interventions. This included data on caregiver knowledge and perceptions about maternal nutrition, caregiver resources (such as education, physical and mental health, decision-making power, and domestic violence) and household resources (such as household composition, socioeconomic status, and food security).